Outstanding aesthetic decoration in the doors of the holy shrines (shrine of Imam Hussein, model): ماهر حسين علي الحبوبي (Al-Academy, 2015)
The problem of the search (how to employ own aesthetic values sculpture prominent decorations doors in the holy shrines) as research aims to detect these formulas employed in relief sculpture in accordance with the aesthetic values of the decorations that add structure in the form of doors shrines dimensions of functional and aesthetic and expressive By selecting the general system configurations spaces for doors and select the components of the structural configurations decorative prominent types (geometric and floral and linear and composite) as well as identify the techniques adopted in the executive configurations doors at the level of raw materials and processors show. Find and define the beauty of decorative formations prominent of all types and formations embodied in the interior and exterior doors and entrances that are at the doors of the holy shrines in Iraq, and the shrine of al-Husseini al-Sharif, in its present Year 1435 A.H. - 2014 A.B.Comprised the theoretical framework Display the following topics: The purpose decorative doors holy shrines and public space for the doors, and regulations in configurations doors, divisions basic space doors, and regulations of formal configurations decorative figures, and variations decorative for those configurations in terms of the fundamentals of building approved where as well as aesthetic formations decorative prominent at the level of raw materials and technology implementation. Depend Search procedures descriptive analytical method, through the research community the original's (21) the doors chosen are elected and deliberate represented by (3) the doors embody the research sample, represented by (the door of Qathi Ilhajaat of woodgrain door, Mr. Ibrahim Al-Mujab of the severity of silver, and the door of Al-Ra’as Al-Sharif of the severity of gold and enamel), which resulted in the analysis process to devising a set of results, including:(1)Stretch the foundations for expanding the vertical extent of the potential space for the doors wide for spatial divisions, had the sculptor and ornate depending on the geometric shape of the door rectangle partition.(2)Dependent structural basis for the formation of the total cross-section of the plurality of organizations use decorative carved and compatibility with the diversification of the formal carved decorations.(3)Light plays an significant role in highlighting the carving technique in aesthetic dimension impart values expressionistic decorative active within the unit.(4)In raw texture within a single winning by technical significant impact on the activation of light as an aesthetic model for the decorative unit.